Best of entrepreneurship education? A curriculum analysis of the highest-ranking entrepreneurship MBA programs. Issue 1 (March 2023) - Tiberius, Victor; Weyland, Michael; Mahto, Raj V.
Abstract: Entrepreneurship education has gained widespread attention in both education practice and research over the past three decades. However, whereas research has a strong focus on its effects and many normative concepts exist, little is known about how entrepreneurship is actually taught. To address this research gap, we conduct a curriculum analysis of the 50 best programs in entrepreneurship, according to the 2018 Financial Times ranking "Top MBAs for Entrepreneurship 2018". In particular, we examine their objectives, learning contents and teaching as well as assessment methods as four major dimensions of a graduate entrepreneurship curriculum. The results show that the programs are primarily business and management programs, with a comparatively small share of entrepreneurship itself. Entrepreneurship-specific goals are entrepreneurial attitudes and competences, such as entrepreneurial leadership, entrepreneurial mindset, entrepreneurial skills, opportunity creation, opportunity identification, and transforming uncertainty into opportunity. The learning contents also focus on business, management, and law, whereas the contents relating to entrepreneurship include entrepreneurial failure, entrepreneurial management, entrepreneurial thinking, and entrepreneurship in general. Teaching methods are mainly the ones usually found in higher education, with business plans and prototyping as additional entrepreneurial ones. Assessment methods do not differ from those in business and management education. Highlights: Entrepreneurship-specific goals are entrepreneurial leadership, mindset, skills, and opportunity creation/identification. The learning contents include entrepreneurial failure, management, thinking, and entrepreneurship in general. Entrepreneurship-specific teaching methods are business plans and prototyping. The programs have a stronger business and management rather than entrepreneurship focus.